2013
DOI: 10.1161/strokeaha.111.670901
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Atrophy is an Independent Risk Factor for Unfavorable Outcome After Spontaneous Supratentorial Intracerebral Hemorrhage

Abstract: Background and Purpose— To investigate the influence of cerebral atrophy on clinical outcome in patients with supratentorial intracerebral hemorrhage. Methods— Computed tomography scans of 320 patients included in a prospective, multicenter trial were used for a segmentation analysis to determine the supratentorial cerebral volume. A logistic regression analysis was used to explore its effect on outcome after 90 days in addition to other clinical and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
(18 reference statements)
1
21
1
Order By: Relevance
“…With regard to brain atrophy, 1 study has shown an association with poor outcome in patients with ICH, using a complex approach to calculate brain volume loss that involved calculating the total bihemispheric volume subtracted by ICH volume and cerebrospinal fluid spaces divided by the total supratentorial intracranial volume using computer-assisted threshold-based planimetric techniques. 18 However, this approach of using planimetric measurements of both hemispheres could be confounded by perihematomal edema and mass effect of the ICH. Thus, we adopted both linear measurements and visual presentation template methods on the contralateral side of the ICH, which being simple and reliable, 11,13,19 could provide useful prognostic information across range of settings without the requirement for special imaging software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to brain atrophy, 1 study has shown an association with poor outcome in patients with ICH, using a complex approach to calculate brain volume loss that involved calculating the total bihemispheric volume subtracted by ICH volume and cerebrospinal fluid spaces divided by the total supratentorial intracranial volume using computer-assisted threshold-based planimetric techniques. 18 However, this approach of using planimetric measurements of both hemispheres could be confounded by perihematomal edema and mass effect of the ICH. Thus, we adopted both linear measurements and visual presentation template methods on the contralateral side of the ICH, which being simple and reliable, 11,13,19 could provide useful prognostic information across range of settings without the requirement for special imaging software.…”
Section: Discussionmentioning
confidence: 99%
“…Achieved BP in the hyperacute phase was measured at 1,6,12,18, and 24 hours post randomization; the means of these 5 measurements were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the choice of candidate variables for univariate and multivariate analyses was not always comprehensive. Ideally, all proposed HE determinants, such as initial haematoma volume [31], time from onset to imaging [32], presence of previous white matter lesions [33,34], haemorrhage location [35] and presence of cerebral atrophy, the latter independently associated with poor outcome [36], should be included not only for the radiological outcome but also for the clinical outcome. …”
Section: Discussionmentioning
confidence: 99%
“…The levels of plasma Aβ may be the result of parenchymal and vessel injury. A recent study 27 found an association between cerebral atrophy and prognosis in patients with ICH and attributed this finding to a pre-existing neurodegenerative disease. Therefore, the clinical outcome is likely to be worse if the parenchymal or vessel amyloid concentrations are high.…”
Section: Strokementioning
confidence: 99%